2021
DOI: 10.1093/jas/skab289
|View full text |Cite
|
Sign up to set email alerts
|

Estimating inbreeding depression for growth and reproductive traits using pedigree and genomic methods in Argentinean Brangus cattle

Abstract: Inbreeding depression reduces mean phenotypic value of important traits in livestock populations. The goal of this work was to estimate the level of inbreeding and inbreeding depression for growth and reproductive traits in Argentinean Brangus cattle, in order to obtain a diagnosis and monitor breed management. Data comprised 359,257 (from which 1,990 were genotyped for 40,678 SNP) animals with phenotypic records for at least one of three growth traits: birth weight (BW), weaning weight (WW) and finishing weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The concordance between our results for BTA6 and BTA14 and other works in tropical composite breeds may be a consequence of strong selection pressure in Brangus towards Angus for growth, meat quality and fertility characteristics. This selection pressure is evidenced by the positive genetic trends for growth and scrotal circumference in the Argentinean Brangus reported in the paper by Forneris et al (2021). In turn, the data available for carcass traits are still scarce to display any genetic trend.…”
Section: Discussionmentioning
confidence: 99%
“…The concordance between our results for BTA6 and BTA14 and other works in tropical composite breeds may be a consequence of strong selection pressure in Brangus towards Angus for growth, meat quality and fertility characteristics. This selection pressure is evidenced by the positive genetic trends for growth and scrotal circumference in the Argentinean Brangus reported in the paper by Forneris et al (2021). In turn, the data available for carcass traits are still scarce to display any genetic trend.…”
Section: Discussionmentioning
confidence: 99%
“…The inbreeding coefficient is usually used to evaluate the degree of inbreeding of individuals. By comparing various methods for calculating the inbreeding coefficient, it was found that the ROH-based inbreeding coefficient was the most accurate and could best reflect the true inbreeding level of individuals [ 32 , 33 , 34 , 35 ]. The average of the samples in this study was 0.049, which showed an upward trend compared with that in 2019 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%